ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI RSIA SITTI KHADIAH 1 PERIODE AGUSTUS-OKTOBER 2019 - Alifia Nurdani Darmawan; Andi Tihardimanto; Najamuddin (Program Studi Akuntansi IKOPIN, 2021)
Preeclampsia is a pregnancy-specific syndrome in the form of decreased organ perfusiondue to vasospasm and endothelial activation. Preeclampsia is a major cause of maternaldeath in the world and is still a threatening problem in pregnancy, especially in developingcountries. The purpose of this study was to describe the factors associated with the incidenceof preeclampsia in pregnant women at RSIA Sitti Kharga 1 Period August-October 2019.This type of research was analytic observational with a cross sectional approach usingprimary data (questionnaires) with interview technique methods. and secondary data, namely(medical records). The research method used the